2023
DOI: 10.26633/rpsp.2023.45
|View full text |Cite
|
Sign up to set email alerts
|

Industrially produced trans fat and saturated fat content of food products in Jamaica

Abstract: Objective. To estimate industrially produced trans and saturated fatty acid levels in foods within the Jamaican food system. Methods. A total of 308 commonly consumed foods were selected for analysis based on their potential to contain trans fatty acids. Samples were collected from supermarkets, convenience stores, and fast-food restaurants. Official methods of gas chromatography for the analysis of fats were used. The results were expressed as grams of fatty acid per 100 g of food sample and percentage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…In our study we evaluated the frequency of consumption of foods rich in saturated fats such as fried chicken, hot dogs, french fries, pizza, hamburger, red meat, among others. The findings of our study are in line with a study that reported that the consumption of red meat and fast foods, such as French fries, pizza, and hamburgers, was consumed more frequently in nonmedical students, as was other ultraprocessed products, such as cookies, cakes, chocolates, chips, or sticks 19 , which are rich in saturated fats and contain trans fats 43 . Similarly, in a recent study that explored food consumption patterns among university students, when asked about their purchasing habits at fast food restaurants, it was found that a significantly higher proportion of non-medical students reported buying this type of food, with 61.19% compared to 57.51% of medical students 37 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study we evaluated the frequency of consumption of foods rich in saturated fats such as fried chicken, hot dogs, french fries, pizza, hamburger, red meat, among others. The findings of our study are in line with a study that reported that the consumption of red meat and fast foods, such as French fries, pizza, and hamburgers, was consumed more frequently in nonmedical students, as was other ultraprocessed products, such as cookies, cakes, chocolates, chips, or sticks 19 , which are rich in saturated fats and contain trans fats 43 . Similarly, in a recent study that explored food consumption patterns among university students, when asked about their purchasing habits at fast food restaurants, it was found that a significantly higher proportion of non-medical students reported buying this type of food, with 61.19% compared to 57.51% of medical students 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar trends were observed in Sweden with the highest total TFA values in 1995–1997 and really low values in 2007 ( 68 ) as well as in Argentina ( 75 ) and Korea ( 76 ). Table 2 summarizes the total TFA values of various food groups based on recent measurements in Thailand ( 77 ), Egypt ( 78 ), Argentina ( 75 ), Spain ( 74 ), Jamaica ( 79 ) and Malaysia ( 80 ). Previous research has shown that both voluntary and regulatory measures to reduce iTFA content in foods have resulted in substantial reductions in global intakes of TFAs over the past two decades ( 61 , 81 , 82 ), including Canada ( 83 ) and the European Union (EU) countries ( 84 ).…”
Section: Fatty Acids In Generalmentioning
confidence: 99%